COMPARISON OF INTRATHECAL NALBUPHINE AND FENTANYL AS ADJUVANTS TO BUPIVACAINE IN SPINAL ANESTHESIA IN PATIENTS UNDERGOING LOWER LIMB SURGERIES - VIRENDRA KISHOR NIMBALKAR; SUNEETA DUTTA; POONAM SHARMA; SOMA PAUL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study is to compare nalbuphine 0.5 mg and fentanyl 25 μg when used as an adjuvant to 0.5% bupivacaine heavy in spinal anesthesia for their effect on the sensory block, motor block, and post-operative analgesia. Methods: After fulfillment of inclusion criteria and after obtaining informed written consent from patients, a group of a total of 80 patients was enrolled and divided in GRP-F and GRP-N equally. (1) Group F: Patients received diluted 25 μg of fentanyl with 3 mL (15 mg) of 0.5% hyperbaric bupivacaine. (2) Group N: Patients received diluted 0.5 mg of nalbuphine with 3 mL (15 mg) of 0.5% hyperbaric bupivacaine. Results: The duration of sensory block and motor block was significantly longer in GRP-F than GRP-N. Post-operative analgesia was comparable in both groups with minimal side effects. Conclusion: Intrathecal fentanyl in post-operative period was found to be significantly better than nalbuphine when used as an adjuvant therapy with 0.5% hyperbaric bupivacaine in elective lower limb surgeries with insignificant adverse effects like hypotension, nausea, and vomiting.